TESTING THE INHIBITION OF SAWO PUTIK EXTRACT AGAINST ESCHERIA COLI (E.COLI) BACTERIA - Nurdin, Ambia; Marlinda, Marlinda; Wahyuni, Srie (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Sapodilla, also known as Manilkara zapota or sawo, is being studied as a potential natural remedy for diarrhea caused by Escherichia coli bacteria. The objective of this research is to investigate the inhibitory effects of sapodilla leaf extract on the growth of Escherichia coli bacteria. The method involves formulating sapodilla leaf extract at various concentrations and dividing them into seven groups, including positive and negative controls. The concentrations tested are 2%, 20%, 25%, 30%, and 50% sapodilla leaf extract. The results indicate that sapodilla leaf extract exhibits a mild inhibitory effect on bacterial growth, measuring 6.9 mm in the inhibition zone. Notably, the 50% concentration of sapodilla leaf extract demonstrates a moderate inhibitory effect, with a larger inhibition zone measuring 29.1 mm. This study sheds light on the potential of sapodilla leaf extract as a natural antimicrobial agent, providing valuable insights for further exploration and development of alternative treatments for Escherichia coli-induced diarrhea.